Reference values of capillary blood volume and pulmonary membrane diffusing capacity in North African boys aged 8 to 16 years - Sonia Rouatbi; Mehdi Khemis; AbdelHamid Garrouch; Helmi Ben Saad (Egyptian Journal of Chest Disease and Tuberculosis, 2014)
Lung diffusing capacity estimated using nitric oxide (NO) as the tracer gas has been proposed as a direct measure of the pulmonary membrane diffusing capacity for NO (Dm) and the pulmonary capillary blood volume (Vc). Thus, the aims of this study were to identify the factors influencing Vc and Dm and to establish linear regression equations for predicting reference values for Vc and Dm in healthy Tunisian boys aged 8 to 16 years. Methods: It is a cross-sectional analytical study. The sample is formed of healthy Tunisian children aged 8 to 16 years. First, subjects responded to a questionnaire. Anthropometric and spirometric data were collected. DLNO and DLCO were measured and Dm and Vc were calculated simultaneously during a single breath maneuver using the double transfer technique for NO/CO. Statistical analyses were carried out using Statistica (Statistica Kernel version 6, StatSoft, 26 France). Significance was set at the 0.05 level. Results: Eighty five boys were included to establish Vc and Dm reference values. Correlations between the Vc or Dm of the 85 healthy boys and anthropometric data showed that only BMI was not significantly correlated with Dm. The proposed Vc reference equation is: Vc (ml) = 11.3859 × age + 3.4613 × BMI − 117.0508. This model explains 45.7% of Vc variability. The proposed Dm reference equation is as follows: Dm (ml/min/mmHg) = 0.6430 × height − 41.5854. This model explains only 16.31% of Dm variability. Conclusion: We have established a reliable and an available reference equation to interpret the results of Dm and Vc in healthy North African boys aged 8 to 16 years.